Enhanced Antibacterial Property by the Synergetic Effect of TiO2 and ZnO Nano-Particles in Biodegradable Hydrogel - Gokmen, Fatma Ozge; Temel, Sinan; Yaman, Elif (European Scientific Journal, ESJ, 2019)
In this study, three types of nanocomposite hydrogel were produced by free radical polymerization and chemical bath deposition technique together. TiO2 nanoparticles (NPs) have been incorporated in polymeric matrices in order to provide antimicrobial activity to the biodegradable hydrogel. Then, ZnO NPs have been deposited on the surface of the hydrogel to improve antibacterial activity. Structural and antibacterial properties of above nanocomposites were fully determined by X-Ray diffractometer (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-Ray Spectrometer (EDX), and ASTME-2149 methods. At the reaction time of 60 minutes, nanoZnO particles on hydrogel were fully developed. Zn content of hydrogel was 35.89 at. %, Ti content of hydrogel was also determined as 0.16 at.%. In respect to antibacterial activity tests results, Escherichia coli were more resistant to hydrogel and ZnO nanoflower than Staphylococcus aureus.